Fetal cardiac filling and ejection time fractions by pulsed‐wave Doppler: reference ranges and potential clinical application. (12th June 2021) - Soveral, I.; Crispi, F.; Guirado, L.; García‐Otero, L.; Torres, X.; Bennasar, M.; Sepúlveda‐Martínez, Á.; Nogué, L.; Gratacós, E.; Martínez, J. M.; Bijnens, B.; Friedberg, M.; et al.
ABSTRACT: Objectives: Fetal cardiac function can be evaluated using a variety of parameters. Among these, cardiac cycle time‐related parameters, such as filling time fraction (FTF) and ejection time fraction (ETF), are promising but rarely studied. We aimed to report the feasibility and reproducibility of fetal FTF and ETF measurements using pulsed‐wave Doppler, to provide reference ranges for fetal FTF and ETF, after evaluating their relationship with heart rate (HR), gestational age (GA) and estimated fetal weight (EFW), and to evaluate their potential clinical utility in selected fetal conditions. Methods: This study included a low‐risk prospective cohort of singleton pregnancies and a high‐risk population of fetuses with severe twin–twin transfusion syndrome (TTTS), aortic stenosis (AoS) or aortic coarctation (CoA), from 18 to 41 weeks' gestation. Left ventricular (LV) and right ventricular inflow and outflow pulsed‐wave Doppler signals were analyzed, using valve clicks as landmarks. FTF was calculated as: (filling time/cycle time) × 100. ETF was calculated as: (ejection time/cycle time) × 100. Intraclass correlation coefficients (ICC) were used to evaluate the intra‐ and interobserver reproducibility of FTF and ETF measurements in low‐risk fetuses. The relationships of FTF and ETF with HR, GA and EFW were evaluated using multivariate regression analysis. Reference ranges for FTF and ETF were then constructed using the low‐risk population. Z ‐scores of FTF and ETF in the high‐risk fetuses were calculated and analyzed. Results: In total, 602 low‐risk singleton pregnancies and 54 high‐risk fetuses (nine pairs of monochorionic twins with severe TTTS, 16 fetuses with AoS and 20 fetuses with CoA) were included. Adequate Doppler traces for FTF and ETF could be obtained in 95% of low‐risk cases. Intraobserver reproducibility was good to excellent (ICC, 0.831–0.905) and interobserver reproducibility was good (ICC, 0.801–0.837) for measurements of all timing parameters analyzed. Multivariate analysis of FTF and ETF in relation to HR, GA and EFW in low‐risk fetuses identified HR as the only variable predictive of FTF, while ETF was dependent on both HR and GA. FTF increased with decreasing HR in low‐risk fetuses, while ETF showed the opposite behavior, decreasing with decreasing HR. Most recipient twins with severe TTTS showed reduced FTF and preserved ETF. AoS was associated with decreased FTF and increased ETF in the LV, with seemingly different patterns associated with univentricular vs biventricular postnatal outcome. The majority of fetuses with CoA had FTF and ETF within the normal range in both ventricles. Conclusions: Measurement of FTF and ETF using pulsed‐wave Doppler is feasible and reproducible in the fetus. The presented reference ranges account for associations of FTF with HR and of ETF with HR and GA. These time fractions are potentially useful for clinical monitoring of cardiac function in severe TTTS, AoS and other fetal conditions overloading the heart. © 2020 International Society of Ultrasound in Obstetrics and Gynecology